2016
DOI: 10.1120/jacmp.v17i2.5868
|View full text |Cite
|
Sign up to set email alerts
|

Commissioning and initial experience with the first clinical gantry‐mounted proton therapy system

Abstract: The purpose of this study is to describe the comprehensive commissioning process and initial clinical experience of the Mevion S250 proton therapy system, a gantry‐mounted, single‐room proton therapy platform clinically implemented in the S. Lee Kling Proton Therapy Center at Barnes‐Jewish Hospital in St. Louis, MO, USA. The Mevion S250 system integrates a compact synchrocyclotron with a C‐inner gantry, an image guidance system and a 6D robotic couch into a beam delivery platform. We present our commissioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 14 publications
0
46
0
Order By: Relevance
“…). For the Mevion S250, the slope of the lexan and lead layers of second scatter are greater near its central axis . Therefore, slight changes in the beam SO (3 mm) produced significant uncertainty on the shape of the profiles, for all the studied options.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…). For the Mevion S250, the slope of the lexan and lead layers of second scatter are greater near its central axis . Therefore, slight changes in the beam SO (3 mm) produced significant uncertainty on the shape of the profiles, for all the studied options.…”
Section: Discussionmentioning
confidence: 94%
“…Zhao et al observed noticeable differences along the field edges, both inside and outside of the fields, at shallow depths. They stated that, the differences were significantly decreased with increasing depth in water …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations